Purity, Victimhood and Agency: Fifteen years of the UN Trafficking Protocol - Wijers, Marjan (Anti-Trafficking Review, 2015)
When the women’s movement reverted back to the nineteenth-century Victorian concept of ‘trafficking in women’ to address abuses of migrant women in the sex industry, it unwittingly adopted not only a highly morally biased concept—dividing women into innocent victims in need of rescue and guilty ones who can be abused with impunity—but also one with racist and nationalistic overtones. Despite efforts to counter these flaws, this inheritance continues to define the debate on trafficking today, exemplified by the distinction made by the United Nations Trafficking Protocol between so-called ‘sexual exploitation’ and ‘labour exploitation’ and its focus on the aspects of recruitment and movement. As a result, its implementation in the last fifteen years has led to a range of oppressive measures against sex workers and migrants in the name of combating trafficking. The focus on the purity and victimhood of women, coupled with the protection of national borders, not only impedes any serious effort to address the exploitation of human beings under forced labour and slavery-like conditions, but actually causes harm. The call of the anti-trafficking movement for a human rights-based approach does not necessarily solve these fundamental problems, as it tends to restrict itself to protecting the rights of trafficked persons, while neglecting or even denying the human rights of sex workers and migrants.